Financial Management and Business Survival Strategies of Micro and Small Enterprise (MSE) Traders in Education Areas (Study on Traders Around the UIN Sunan Ampel Surabaya Campus) - Syahrul Ulum; Novie Andriani Zakariya; Izzatul Millah (CV. Satria Jaya, 2025)
This study examines financial management practices and survival strategies adopted by Micro and Small Enterprise (MSE) traders operating in education areas, using a case study of traders around UIN Sunan Ampel Surabaya. Employing a qualitative case study approach, data were collected through in-depth interviews with seven informants representing two MSE business units. The findings reveal that planned and adaptive financial management, including simple bookkeeping, separation of personal and business finances, and value-based financial discipline, play a crucial role in sustaining business operations amid fluctuating student demand. Social relationships, motivation, and ethical considerations further shape traders’ survival strategies in responding to economic uncertainty. This study contributes to the literature by highlighting the integration of financial management and social-contextual strategies in sustaining MSEs within education-based economic environments.